MALAYSIAN WEB SEARCH ENGINES: A CRITICAL ANALYSIS - Halim, Hananzita; Kaur, Kiran (Malaysian Journal of Library and Information Science, 2006)
This paper reports the results of a study conducted to explore and compare the features of independently built Malaysian Web search engines, as well as evaluate their performance and search capabilities. Four Malaysian independently built search engines were chosen for the study and Google served as the benchmark engine. This study applied two co-related methodologies, namely Information Retrieval Evaluation Methodology and common features comparison. The Information Retrieval Evaluation Methodology measures include search capabilities, retrieval performance (recall & precision) and user effort. Results show that each search engine portrays different strengths and weaknesses. Malaysia Directory appears to be the best Malaysian Web search engine in term of feature presentation but fails in term of retrieval performance; whereas Malaysia Central managed to score the highest for mean precision but failed to excel in terms of feature presentation. SajaSearch outperformed Cari in most related documents, even though Cari did return the highest total hits. Overall comparison with Google leaves Malaysian search engines with much to improve on in terms of performance and search capabilities. Implications for the design of Malaysian Web Search Engines are also discussed.